Modelling the development of biological structures displaying longitudinal geometries in vitro: culturing pluripotent stem cells on plasma-treated, growth factor-coupled polycaprolactone fibres - Badwi B. Boumelhem; Stuart T. Fraser; Syamak Farajikhah; Rachel A. Shparberg; Michael B. Morris; Marcela M.M. Bilek; Anyu Zhang; Behnam Akhavan; Simon Fleming; Maryanne Large (Engineered Regeneration, 2024)
Many biological structures such as nerves, blood and lymphatic vessels, and muscle fibres exhibit longitudinal geometries with distinct cell types extending along both the length and width of internal linear axes. Modelling these three-dimensional structures in vitro is challenging: the best-defined stem-cell differentiation systems are monolayer cultures or organoids using pluripotent stem cells. Pluripotent stem cells can differentiate into functionally mature cells depending on the signals received, holding great promise for regenerative medicine. However, the integration of in vitro differentiated cell types into diseased tissue remains a challenge. Engineered scaffolds can bridge this gap if the appropriate signalling systems are incorporated into the scaffold. Here, we have taken a biomimicry approach to generate longitudinal structures in vitro. In this approach, mouse embryonic stem cells are directed to differentiate to specific cell types on the surface of polycaprolactone (PCL) fibres treated by plasma-immersion ion implantation and to which with lineage-specifying molecules have been covalently immobilised. We demonstrate the simplicity and utility of our method for efficiently generating high yields of the following cell types from these pluripotent stem cells: neurons, vascular endothelial cells, osteoclasts, adipocytes, and cells of the erythroid, myeloid, and lymphoid lineages. Strategically arranged plasma-treated scaffolds with differentiated cell types could ultimately serve as a means for the repair or treatment of diseased or damaged tissue.